Foundations of Analytical Chemistry - Cases, Miguel Valcárcel; López-Lorente, Ángela I.; López-Jiménez, Ma Ángeles (Springer, 2018)
The authors were compelled to write this book by two main “drivers.” One was their wish to further endorse the strategic significance of the true fundamentals of Analytical Chemistry in order to help students first approaching this discipline to understand them and to erect their “analytical chemical building” on solid foundations.
A Teaching–Learning Approach